Students’ misconceptions about bonding and chemical structure in chemistry - Gudyanga, Ephias; Madambi, Tawanda (Midlands State University, 2015)
This paper sought to find out the students’ misconceptions about bonding and chemical structure in Chemistry at secondary school level. Simple descriptive survey was the main design. Participants were comprised of eighty (80) randomly sampled out Form 3 and Form 4 pupils. A 15 point Likert Scale (test) and a group interview were used as data collection instruments. There was a concordance in the sets of findings using descriptive statistics, inferential statistics and interviews showing that students had misconceptions in strengths of chemical bonds (89%, F4df=11.35;p<0.05), shapes of molecules (75%; F1df =10.39; p<0.05), coordinate bonding (68%, F2df =14.56; p<0.05), molecular / ionic charges (61%, F 2df=11.33; p<0.05) and hydrogen bonding 60%, F4df=10.49;p<0.05). It was recommended that ways of minimizing students’ misconceptions could include use of conceptual chemical models, use of e-learning for example Cyber School. Learning environments should be more visual than conceptual. Science teachers should be equipped with the various strategies for teaching skills so as to improve teaching and learning in science.